1988
DOI: 10.1136/bmj.296.6636.1575
|View full text |Cite
|
Sign up to set email alerts
|

Serological markers of renal itch in patients receiving long term haemodialysis

Abstract: Although we cannot exclude an unknown interaction between coeliac disease and chronic myeloid leukaemia in our patient, we think that preexisting hyposplenism may have favourably influenced the course of her leukaemia.We thank Dr L M Wiedman, Chester Beatty Laboratories, London, for the DNA analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2
8

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 2 publications
3
28
2
8
Order By: Relevance
“…The role of secondary hyperparathyroidism in uremic pruritus is controversial. Our investigation, in agreement with Tarng et al [15] and Carmichael et al [2], revealed no substantial difference in serum iPTH values among our patients with or without severe pruritus. It is likely that hpyerparathyroidism is not responsible for severe pruritus in our patients.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The role of secondary hyperparathyroidism in uremic pruritus is controversial. Our investigation, in agreement with Tarng et al [15] and Carmichael et al [2], revealed no substantial difference in serum iPTH values among our patients with or without severe pruritus. It is likely that hpyerparathyroidism is not responsible for severe pruritus in our patients.…”
Section: Discussionsupporting
confidence: 82%
“…Our data, in agreement with those of Balaskas et al [6], further support the observation that dialysis adequacy was not the single factor contributing to pruritus. The relationship between biochemical characteristics and PS is still questionable although many hypotheses have been advanced [1][2][3][4][5]. The lack of an association is supported by our failure to establish a relationship between clinical parameters and PS in our CAPD population (table 3).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…In the published literature [4][5][6][7][8], these authors suggest ed that the deranged metabolism of divalent ions, i.e. hypercalcemia, hyperphosphatemia and high calciumphosphorus product, is the serological marker of renal itching in certain uremic patients.…”
Section: Discussionmentioning
confidence: 99%
“…In one recent study, 37 dialysis patients with secondary hyperparathyroidism and pruritus underwent parathyroidectomy leading to a statistically significant decrease in pruritus scores [52]. In spite of these facts, no correlation between parathormone (PTH) levels and intensity of itching was found in most of the studies [9,42,45]. PTH itself is not pruritogenic when injected into the skin [53].…”
Section: Hyperparathyroidismmentioning
confidence: 99%